Modification of hypertension treatment in old persons with diabetes type 2 - Kowrach, Marek; Luźniak, Paweł; Marek, Jerzy (Przewodnik Lekarza/Guide for GPs, 2009)
Hypertension is an important risk factor determining prognosis of older diabetic type 2 patients. Effective treatment of hypertension decreases the number of complications in this particular group of patients, especially decreasing the macrovascular complications influencing the high mortality rates among them. Target blood pressure is not determined, but among many old diabetic patients it can be set as 80 years old larger values of blood pressure are acceptable. The main group of drugs which should be used in hypertension treatment comprises drugs blocking RAAS, and such treatment is part of the wide intervention of multiple risk factor therapy.